FinTech, General Purpose Technology und Wohlfahrt - Johannes Treu (IU Internationale Hochschule, 2022)
– FinTech is said to have promising effects. The consideration that arises is whether this new form is a special kind of technology that affects an entire economy and has the potential to change societies through its impact on existing economic and social structures. Thus, the question arises whether FinTech can be characterized as general-purpose technology (GPT)? This is followed by the second question: What is the impact of FinTech at the aggregate level and as a potential GPT on aggregate economic welfare? Using two different GPT definitions and characteristics, we show how FinTech can be characterized as a GPT. In the second part, an analytical framework is used to show that FinTech increases welfare as a positive supply shock.
urn:nbn:de:101:1-2022062812374702308553
Keywords: G20; G23; O10; O30; O33; O49; 650; Fintech; Finanztechnologie; Wohlfahrt; AS-AD Modell; General Purpose Technology; GPT